High‐altitude incoherent‐scatter measurements at Jicamarca - Hysell, D. L. (2017)
In an attempt to reproduce experimental results obtained in the early days of operations, electron density profiles have been measured at the Jicamarca Radio Observatory at altitudes reaching L=2. The methodology involves using a combination of pulses, including pulses as long as 4 ms, and processing the data with matched filtering. The modern experiments are complicated by systemic, time‐dependent bias in the noise estimators as well as by clutter from satellites and space debris, including a geosynchronous satellite. Ultimately, experiment performance comparable to what was achieved in the original experiments could be achieved and should be surpassed in future experiments when all four of the Jicamarca transmitters will be utilized.